PENGARUH KOMPENSASI, BEBAN KERJA DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN NON ASN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING DI RSUD BESUKI SITUBONDO - Ahmad Zaini; Ika Wahyuni; Minullah Minullah (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
In response to issues related to compensation and workload, RSUD Besuki Situbondo has taken the initiative to reduce these challenges by fostering a comfortable work culture and providing complete facilities. The hospital also promotes job satisfaction among employees through appreciation and support for personal and professional development. Thus, compensation, workload, work culture, job satisfaction, and employee performance are closely interconnected. This study aims to analyze and examine the influence of compensation, workload, and work culture on the performance of non-civil servant (non-ASN) employees, with job satisfaction as an intervening variable at RSUD Besuki Situbondo. This is a quantitative research study involving a population of 67 non-ASN employees. The sampling technique used was proportional stratified random sampling, applied to a population with hierarchical or layered structures. Data analysis and hypothesis testing were conducted using the Structural Equation Modeling – Partial Least Square (PLS-SEM) method. The results of direct effect hypothesis testing using Smart PLS 3.0 indicate that compensation, workload, and work culture all have a significant positive effect on job satisfaction. Additionally, compensation, workload, and work culture also significantly and positively affect employee performance. Job satisfaction itself has a significant positive impact on performance. Furthermore, the indirect effect analysis shows that compensation, workload, and work culture significantly and positively affect performance through job satisfaction.